Colour and stability of pure anthocyanins in aqueous solutions at high pH values - Andersen, Øyvind M. (2011)
This study on anthocyanin colour variation (intensity, lambda max, molar absorbptivity) over the pH range 1-9 during 60 days of storage, was conducted on petunidin 3-[6-O-(4-O-E-p-coumaroyl-O-alfa-L-rhamnopyranosyl)-beta-D-glucopyranoside]-5-O-beta-D-glucopyranoside (petanin) and cyanidin 3-O-beta-D-glucopyranoside (cy3glc) at 10 and 23ºC. Compared to cy3glc, petanin afforded higher colour intensity and higher or similar stability throughout the whole pH range. At pH 4.0, 84% of petanin was intact after 60 days storage at 10ºC, while the corresponding solution of cy3glc was totally degraded. At pH 8.1 the colour intensity of petanin was even higher than at the lowest pH values. The visible lmax absorption of petanin after 5 days at pH 8.1 at 10ºC was similar or higher than the corresponding absorptions of the fresh solutions of cy3glc at any pH. The use of anthocyanins like petanin as food colorants in slightly alkaline products (bakery, milk, egg, etc.) should therefore be considered at least in products with limited storage time kept in a refrigerator.